Proximal Convoluted Tubules as the Primary Target of Renal Histopathological Injury by Ingestion of Pesticide-Residue-Laden Fruits and Vegetables - Lubna Shahper , Shagufta Nasreen , Muhammad Qasim Muneer , Nazia Ayyub , Sadia Hassan (Journal of Islamic International Medical College, 2021)
Objective: To determine the potential adverse renal histopathological effects on the proximal convoluted tubules in male, Wistar rats due to ingestion of subchronic dose of triazophos. Study Design: Randomized controlled trial. Place and Duration of Study: A study of 3 weeks duration (plus 1 week for slide preparation & histological study), was held in the animal house-PGMI, Bird wood road, Lahore. Materials and Methods: Two equal groups were made, of 6 Wistar, male rats each. Group A was control while experimental group B was given triazophos, in a dose of 8.2 mg/kg-subchronic dose (1/10 of LD 50), a commonly used pesticide, as 1:100 dilution solution through oral gavage for 21 consecutive days. On day 22, the rats were sacrificed and tissues preserved for histological examination and measurement of proximal and distal tubular diameters by using micrometric grid. Results: The micrometric measurement of diameters of PCT in group A and B indicated that they increased significantly from 38.90 ± 2.72μm in group A to 50.35 ± 2.61μm in group B (p-value <0.001). The mean diameter of DCT in both the groups was also measured and increased in group B from 34.48 ± 2.58μm in group A to 48.03 ± 3.42μm in group B (p-value <0.001). In group B, inflammatory changes like basement membrane interruption, loss of brush border and severe vacuolar cellular degeneration of proximal convoluted tubules were seen. Conclusion: The results confirm the potential adverse renal histopathological effects on the proximal convoluted tubules in male, Wistar rats due to ingestion of triazophos, a commonly used pesticide. Pesticides induce inflammatory changes in convoluted tubules leading to tubular dilatation and hyperplasia more in PCT owing to the extensive exposure of toxic substances in the proximal tubules and resultant increased PCT mean diameter.